2022
DOI: 10.1186/s43251-022-00067-w
|View full text |Cite
|
Sign up to set email alerts
|

Damage characterization and resilience optimization of reinforced concrete bridge piers under vehicle impact

Abstract: Vehicle impact creates a dynamic loading condition at high strain rate exhibiting a unique interaction with the resisting structural members’ material properties. This interaction results in an increase in the material’s strength properties, a behavior captured in analysis via the computation of a strength factor known as the dynamic increase factor (DIF). In reinforced concrete (RC) bridge piers, the concrete cover receives the initial impact from the vehicle, causing damage to this exterior surface. This mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Prototyped ABC pier with lower concrete strength has been utilized [7] to estimate damage of the coupler-rebar region incurred by impact. The impact of the pier specimen is subjected to the concrete strength parameters due to its high vulnerability to vehicle impact due to its exposed surface area quantifying a good composition between the shear capacity to primarily resist the impact load, and the flexural capacity predominately control the serviceability of the pier [5]. However, this present study intends to quantify the coupler high velocity post vehicle impact behavior at high strain rate load incurred by semi-trailer on the representative prototyped half sized ABC pier.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prototyped ABC pier with lower concrete strength has been utilized [7] to estimate damage of the coupler-rebar region incurred by impact. The impact of the pier specimen is subjected to the concrete strength parameters due to its high vulnerability to vehicle impact due to its exposed surface area quantifying a good composition between the shear capacity to primarily resist the impact load, and the flexural capacity predominately control the serviceability of the pier [5]. However, this present study intends to quantify the coupler high velocity post vehicle impact behavior at high strain rate load incurred by semi-trailer on the representative prototyped half sized ABC pier.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic Impact Factor (DIF) can be evaluated from Equation 5 by using ξ computed from Equation 4 [37,38]. 𝐷𝐼𝐹 = ( έ 10 −4 ) 𝜉 (5) where: DIF is the Dynamic Impact Factor, ξ is dynamic parameter, and έ is the Quasi-static strain rate of steel re-bar. Equation 5 yields the analytical DIF result as 1.053.…”
Section: Determination Of Dynamic Increase Factor (Dif)mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the structural reliability of RC piers subjected to sequential loading exerted by blast and vehicular impact were also studied. The study showed that the structural performance of the piers are particularly sensitive to its dimensions [31,39]. This implies that an increase in the stiffness of the pier could possibly help it withstand the external forces caused by vehicular impact.…”
Section: Introductionmentioning
confidence: 98%